The effect of stem cell viability and storage time - Medeni, S. Solmaz; Ozsan, G.; Acar, C.; Sevindik, O.; Turkyilmaz, D.; Demirkan, F.; Undar, B. (Nature Publishing Group, 2016)
[Abstract Not Available]
42nd Annual Meeting of the European-Society-for-Blood-and-Marrow-Transplantation -- APR 03-06, 2016 -- Valencia, SPAIN